A transcriptome analysis uncovers Panax notoginseng resistance to Fusarium solani induced by methyl jasmonate - Diqiu Liu; Qin Zhao; Xiuming Cui; Rui Chen; Xin Li; Bingling Qiu; Feng Ge (Genes & Genomics, 2019)

Yeast cell walls stimulate viability, respiratory burst, and phagocytosis in channel catfish (Ictalurus punctatus) head-kidney macrophages - Jianjun Zhou; Zhen Gao; Wenbiao Wang; Feng Huang; Junpeng Hu; Aqiong Gong; Rui Wang; Wumin Yang; Jie Li; Xianqin Hu; Xuedong Wang (Aquaculture International, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Soil water content and pH drive archaeal distribution patterns in sediment and soils of water-level-fluctuating zones in the East Dongting Lake wetland, China - Wei Li; Defeng Feng; Gang Yang; Zhengmiao Deng; Junpeng Rui; Huai Chen (Environmental Science and Pollution Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

Selenium alleviates cadmium-induced inflammation and meat quality degradation via antioxidant and anti-inflammation in chicken breast muscles - Kou-Kou Tang; Hui-Qin Li; Kui-Chao Qu; Rui-Feng Fan (Environmental Science and Pollution Research, 2019)

Selenium-Yeast Alleviated Inflammatory Damage Caused by Lead via Inhibiting Ras/ERK Pathway and Inflammatory Factors in Chicken Skeletal Muscles - Zhe Liu; Feng Zhang; Ping Lu; Rui Zhao; Hua Zhang; Baifen Song; Liyang Li; Zhijun Wu; Rui Wu (Biological Trace Element Research, 2019)

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Inhibition of YAP with siRNA prevents cartilage degradation and ameliorates osteoarthritis development - Yong Gong; Song-Jian Li; Rui Liu; Jian-Feng Zhan; Chao Tan; Yi-Fei Fang; Yan Chen; Bo Yu (Journal of Molecular Medicine, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)